LB1.6 Neisseria meningitidis carriage among men who have sex with men – new york city, 2016–2017. (8th July 2017) - Pathela, Preeti; Ngai, Stephanie; Bell, Julie Anne; Majrud, Difaa; Zayas, Geicy; Crawley, Addie; Macneil, Jessica; Weiss, Don
Abstract : Introduction: There have been recent U.S. outbreaks of N. meningitidis (Nm) serogroup C among men who have sex with men (MSM). From 1/2012-6/2015, 1/3 of U.S. cases in MSM were from New York City (NYC); 65% were HIV+. Little is known about Nm carriage among MSM and potential sexual transmission of Nm. Methods: We conducted a carriage study among a sample of MSM and transgender female patients at 2 NYC sexual health clinics (6/2016-2/2017). Clinicians collected oropharyngeal (OP), rectal, and urethral specimens for Nm culture and STD testing. We matched test results with patient self-administered questionnaire data on antibiotic use, meningococcal vaccine history, and sexual risk behaviours (past 30 days), and data extracted from clinic medical records and the NYC STD registry (past 3 months). We calculated carriage prevalence by serogroup (slide agglutination) and anatomic site; examined Nm-gonorrhoea (GC) co-infection; and assessed associations between patient characteristics and carriage at any site using logistic regression. Results: Of 636 study patients, 146 (23%; 95% CI 20%–26%) were Nm carriers. Serogroup distribution of OP carriage (22.4%; 142/633) was: 59% non-groupable, 37% B, 1.4% C, 0.7% W, 1.4% Y. Of OP Nm carriers, 20 (14%) were OP GC-positive. Urethral (0.5%; 3/626) and anal (1%; 6/626) carriage prevalence were low. Any-site carriage was associated with: kissing (OR 3.2; 95% CI 1.1–9.3), performing oral sex (OR 2.0; 95% CI 1.1–3.6), attending bars/clubs (OR 1.6; 95% CI 1.1–2.6), and antibiotic use (OR 0.2; 95% CI 0.1–0.5); and not associated with HIV status, STD history, or vaccine status. In multivariable analyses, only antibiotic use was associated with carriage. Conclusion: Nm carriage in our large patient sample did not match Nm outbreak patterns (e.g., paucity of serogroup C, no link with HIV). The OP carriage rate was similar to that in prior studies, but with higher serogroup B. Low prevalence of urethral and rectal Nm carriage and lack of association with STD risk factors suggests that sexual transmission of Nm might be uncommon in this population.